A narrative review of circulating tumor cells clusters: A key morphology of cancer cells in circulation promote hematogenous metastasis - Chen, Qiong; Zou, Jueyao; He, Yong; Pan, Yanhong; Yang, Gejun; Zhao, Han; Huang, Ying; Zhao, Yang; Wang, Aiyun; Chen, Wenxing; Lu, Yin (Frontiers in Oncology, 2022)
Circulating tumor cells (CTCs) that survive in the blood are playing an important role in the metastasis process of tumor. In addition, they have become a tool for tumor diagnosis, prognosis and recurrence monitoring. CTCs can exist in the blood as individual cells or as clumps of aggregated cells. In recent years, more and more studies have shown that clustered CTCs have stronger metastasis ability compared to single CTCs. With the deepening of studies, scholars have found that cancer cells can combine not only with each other, but also with non-tumor cells present in the blood, such as neutrophils, platelets, etc. At the same time, it was confirmed that non-tumor cells bound to CTCs maintain the survival and proliferation of cancer cells through a variety of ways, thus promoting the occurrence and development of tumor. In this review, we collected information on tumorigenesis induced by CTC clusters to make a summary and a discussion about them. Although CTC clusters have recently been considered as a key role in the transition process, many characteristics of them remain to be deeply explored. A detailed understanding of their vulnerability can prospectively pave the way for new inhibitors for metastasis.